2017
DOI: 10.1103/physrevd.96.114019
|View full text |Cite
|
Sign up to set email alerts
|

Universality of the underlying event in pp collisions

Abstract: In this paper we study ATLAS results on underlying event in pp collisions at √ s = 0.9, 7 and 13 TeV. We show that the center-of-mass energy dependences of the charged-particle production sensitive to the underlying event ("transverse" region) and to the hardest partonic interaction ("towards" and "away" regions) in pp collisions can be both understood in terms of the change of the inclusive average multiplicity. Within uncertainties, the corresponding particle production as a function of the leading charged p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Motivated by the results of our previous work [26], where we shown that the 282 particle production sensitive to the underlying event (UE observables) exhibited an approximate KNO scaling. In this paper we investigated in more detail the scaling properties using data from three experiments at the LHC, as well as We studied the number density in the transverse side divided by the charged- particle density in inelastic pp collisions (KNO variable).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Motivated by the results of our previous work [26], where we shown that the 282 particle production sensitive to the underlying event (UE observables) exhibited an approximate KNO scaling. In this paper we investigated in more detail the scaling properties using data from three experiments at the LHC, as well as We studied the number density in the transverse side divided by the charged- particle density in inelastic pp collisions (KNO variable).…”
Section: Resultsmentioning
confidence: 91%
“…Little or no energy dependence is observed after the implementation of the scaling factor. This is 117 what we called "universality of UE" in our previous work where p leading T was used instead [26]. The results are compared with PYTHIA 8 simulations since it reproduces very well many features of LHC data.…”
mentioning
confidence: 87%
“…At the LHC energies, MPI is the process which occurs at a substantial rate in hadronic collisions and is a very important ingredient in explaining the multiplicity dependence of various observables. MPI incorporated in PYTHIA8, is able to describe many of the experimentally observed features, such as multiplicity distribution and underlying events; light-flavour and heavy-flavor production; and together with color-reconnection, it is able to reproduce flow-like patterns in pp collisions [39][40][41][42][43][44]. Models containing MPI well describe the multiplicity dependence of J/ψ production and thus reveal that MPI is an important mechanism behind the production of J/ψ [7,35].…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between particle production at high transverse momentum and the large underlying event activity has been extensively documented for pp and p-Pb collisions [16,17,18,19,20]. Namely, for small systems the underlying event activity increases with increasing the leading particle transverse momentum.…”
mentioning
confidence: 99%